Cathepsins and Their Endogenous Inhibitors in Host Defense During Mycobacterium tuberculosis and HIV Infection - Anes, Elsa; Azevedo-Pereira, José Miguel; Pires, David (Frontiers in Immunology, 2021)
The moment a very old bacterial pathogen met a young virus from the 80’s defined the beginning of a tragic syndemic for humanity. Such is the case for the causative agent of tuberculosis and the human immunodeficiency virus (HIV). Syndemic is by definition a convergence of more than one disease resulting in magnification of their burden. Both pathogens work synergistically contributing to speed up the replication of each other. Mycobacterium tuberculosis (Mtb) and HIV infections are in the 21st century among the leaders of morbidity and mortality of humankind. There is an urgent need for development of new approaches for prevention, better diagnosis, and new therapies for both infections. Moreover, these approaches should consider Mtb and HIV as a co-infection, rather than just as separate problems, to prevent further aggravation of the HIV-TB syndemic. Both pathogens manipulate the host immune responses to establish chronic infections in intracellular niches of their host cells. This includes manipulation of host relevant antimicrobial proteases such as cathepsins or their endogenous inhibitors. Here we discuss recent understanding on how Mtb and HIV interact with cathepsins and their inhibitors in their multifactorial functions during the pathogenesis of both infections. Particularly we will address the role on pathogen transmission, during establishment of intracellular chronic niches and in granuloma clinical outcome and tuberculosis diagnosis. This area of research will open new avenues for the design of innovative therapies and diagnostic interventions so urgently needed to fight this threat to humanity.